Efeitos da crioterapia sobre a estrutura e função dos tendões: uma revisão sistemática - Lima, Tatiana Araujo (2025)
Cryotherapy is widely used in the treatment of soft tissue injuries; however, questions remain regarding the alignment between its scientific foundations and clinical application. While most evidence supporting cryotherapy stems from animal models, there is a lack of robust data in human subjects. Given the heterogeneous nature of soft tissues—including muscles, tendons, and ligaments—it is crucial to understand how cold exposure affects each tissue type. Tendons, in particular, play a central role in musculoskeletal health, and better understanding their response to cryotherapy is essential, especially in the context of tendinopathy—a condition with rising prevalence across age groups worldwide. This systematic review aimed to analyze studies investigating the clinical, mechanical, and physiological effects of cryotherapy on human tendons. A comprehensive search was conducted across multiple databases, including CENTRAL, MEDLINE (via PubMed), EMBASE, CINAHL, and PEDro. Studies were included if they involved human participants, applied cryotherapy as an intervention, and assessed outcomes related to healthy or pathological tendons. The search retrieved 1,034 articles, of which twelve met the inclusion criteria. Among these, six (50%) evaluated mechanical outcomes, five (41.7%) focused on physiological parameters, and five (41.7%) investigated clinical outcomes related to pain and function. The findings suggest that cryotherapy may contribute to pain reduction, especially when combined with other therapeutic strategies such as exercise or ultrasound. Nonetheless, the studies reviewed presented notable methodological limitations, highlighting the need for more rigorous research in this area.